(untitled) (PANGEEA, 2026)
When considering development of human society, it is more than obvious that it registered huge advances, especially in the last century in diverse human-related activity fields, fact that has been possible without any doubt because of applying diverse technologies which need for their operation energy resources among other material resources. Recorded progress in technological field was possible based on using fossil fuels for electric and thermal energy supply, which have had as a result not only positive impacts anyway but also undesired ones in form of environmental pollution. Nowadays, debated climate change and global warming as effect of huge CO2 emissions is bringing new innovative targets on the base of applying renewable energy resources for assuring electricity supply in a sustainable manner. Much discussed renewable energy resources have materialized in solar energy, wind power, hydro power, and bioenergy. By considering single renewable energy resouces as well as natural geographical conditions in Arab World represented by high levels of solar radiation, existing odds for electricity supply based on solar power by photovoltaic panels are pointed out by taking into account regional differences. Following this target, a case study for some Arab countries will be presented about solar energy usage possibilities by photovoltaic panels systems. Finally, some conclusions will be drawn about real applying odds of renewable energy resources in Arab World for warranting sustainable energy supply of human society in this part of the world.